Analysis Bibliometrics Application of Technology Acceptance Model in Islamic Fintech - Pulungan, Ismail; Ritonga, Juliani; Binti Abu Hasan, Nurul Widad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
ABSTRACT The rapid advancement of technology has led to the emergence of Islamic fintech as an innovation in digital financial services with the potential to enhance financial inclusion. However, public understanding of its use remains limited, resulting in cases of misuse and losses for users and companies alike. This study aims to analyze the factors influencing the acceptance of Islamic fintech using bibliometric methods. Employing a qualitative descriptive approach, data was collected through the Publish or Perish software and analyzed using VOSviewer to map the development of research on the Technology Acceptance Model (TAM) in Islamic fintech. The findings reveal significant growth in Islamic fintech journal publications in 2020, with